Flutter suppression of wind turbine blade based on nonlinear block backstepping control. Issue 1 (November 2020) - Yi, Chenghong; Wang, Yingbo; Sun, Haipeng; Sun, Changle; Zhang, Xiaolin; Li, Shanyao; Liu, Tingrui
Abstract: Aiming at solving the nonlinear flutter problem of aeroelastic system of wind turbine blades, a controller combing block backstepping control and variable pitch motion was designed. Based on the typical blade-section model of the spring-mass-damper and the second-order model of the pitch actuator, nonlinear aeroelastic equation of the system under steady aerodynamic was given. Considering the multivariable, strong coupling factors and the unitary pitch control of the wind turbine blade aeroelastic system, a state space equation for a single-input/multiple-output nonlinear model was deduced. Based on the principle of block control, a nonlinear system with block control standard was obtained, which was composed of two subsystems. In order to suppress blade flutter and protect the blade, backstepping control was used to control blade pitch motion. The nonlinear block backstepping controller was designed by constructing Lyapunov function, and time response which can track the dynamic error of system was demonstrated. The simulation results showed that the designed controller can converge the divergent chattering trend to zero, and make the system globally stable.